IMMIGRATION POLYTECHNIC SOCIALIZATION WITH THE PRIVATE VOCATIONAL SCHOOL OF THE CLASS I IMMIGRATION OFFICE FOR NON TPI JAKARTA CENTER TO SMAN 5 JAKARTA - Seno Pujonggo; Feni Yuli Triani (Jurnal Abdimas Imigrasi, 2020)
Immigration Polytechnic socialization can be used as a means to introduce and educate and provide more knowledge in society. As we know, many common people do not know what immigration is and the existence of the Immigration Polytechnic. For this reason, it is necessary to socialize and introduce immigration Polytechnic as a form of Community Service for Immigration Polytechnic Cadets who carry out Real Work Lectures (KKN) at the Class I Non-TPI Immigration Office in Central Jakarta. Therefore, socialization, introduction and questions and answers were conducted with students of SMA Negeri 5 Central Jakarta together with Immigration Polytechnic Cadets and accompanied by the Public Relations Team of the Class I Non TPI Central Jakarta Immigration Office. The output to be produced from this activity is the formation of students' understanding of SMAN 5 Central Jakarta about immigration Polytechnic education so as to increase the attractiveness of students / I to register as candidates for state civil servants who will serve in the field of immigration and produce articles that can be published in journals. scientific